The Relationship between Peer Social Support and Flourishing Personality Tendencies in Malahayati University Students - adinda; Lutfianawati, Dewi (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
Students face various new demands in their lives, such as academic workloads and environmental demands. In their lives, students are often faced with various situations that impact their level of flourishing. Students with high levels of flourishing are more likely to navigate their college life. Peer social support and personality are factors that influence an individual's level of flourishing. Therefore, the purpose of this study was to determine the relationship between peer social support and personality tendencies and flourishing in students. The subjects were 271 students at Malahayati University. The measurement instruments used in this study were the PERMA Scale, the PSS-FR Scale, and the Big Five Scale. The results showed that peer social support and personality tendencies simultaneously had a relationship with flourishing, and that neuroticism had no partial relationship with flourishing in students at Malahayati University. The implications of this research can serve as input for students to improve their flourishing and achieve optimal levels, enabling them to successfully complete their studies.